Small shelly fossils from the argillaceous facies of the Lower Cambrian Forteau Formation of western Newfoundland ... - Skovsted, Christian B.; Peel, John S. (Zenodo, 2007)
Skovsted, Christian B., Peel, John S. (2007): Small shelly fossils from the argillaceous facies of the Lower Cambrian Forteau Formation of western Newfoundland. Acta Palaeontologica Polonica 52 (4): 729-748, DOI: 10.5281/zenodo.13741171 ...